Contribuições da reconstrução racional didática no desenvolvimento de concepções epistemologicamente mais aceitáveis sobre a natureza da ciência e do progresso científico - Silva, Osmar Henrique Moura da; Laburú, Carlos Eduardo; Nardi, Roberto [UNESP] (FapUNIFESP (SciELO), 2012)
This study inserts itself in the research line conceptions on the nature of the science (CNC) in the school atmosphere. More specifically, on that teacher of natural sciences who claims not to be interested in philosophy, it is usually noticed a tendency to understand and to teach a vision of a ready/ finished and unalterable science, which directly influences the students conception of science. Discussed here is the application of a didactic rational reconstruction in high school, the results of which are compatible with a more epistemologically acceptable educational concep tion on the nature of science as something provisory, variable and controversial.

Este estudo insere-se na linha de pesquisa das concepções sobre a natu reza da ciência (CNC) no ambiente escolar. Mais especificamente, naquele professor de ciências naturais que diz não se interessar pela filosofia, normalmente se nota uma tendência de se entender e se ensinar uma visão de ciência pronta/acabada e imutá vel, que influencia diretamente a concepção de ciência nos estudantes. Realiza-se a aplicação de uma reconstrução racional didática no ensino médio cujos resultados vão ao encontro da concepção educacional mais epistemologicamente aceitável sobre a natureza da ciência como algo provisório, variável e controverso.
Contributions of didactic rational reconstruction in the development of more acceptable epistemological conceptions on the nature of science and scientific progress
Keywords: Rational didactic reconstruction; History and philosophy of the sciences; Secondary schools; Reconstrução racional didática; História e filosofia da ciência; Ensino médio